Rethinking treatment failures. Research on a group of Italian psychotherapists - Oasi, Osmano; De Salve, Francesca; Rossi, Chiara; Maggio, Simone; Casabona, Ilaria; Molgora, Sara (Frontiers in Psychology, 2024)
Introduction. Psychotherapeutic failures involve situational, relational, and personal factors. Dropout refers to a patient's unilateral termination of treatment without the therapist's knowledge or approval.Premature termination occurs when therapy is discontinued before achieving a sufficient reduction in initial problems. Objective. This study explores the role of therapist's emotional response (countertransference), gender, psychotherapeutic orientation, and patient diagnosis in the context of psychotherapeutic failures. Method. A mixed-method approach was used. 59 Italian psychotherapists, practicing mostly privately with at least 5 years of experience, were recruited through Italian professional internet websites. The Therapist Response Questionnaire and the Impasse Interview were administered to each psychotherapist. Each therapist was asked to reflect on their last dropout patient.Quantitative (MANOVA) and qualitative analyses (textual content analysis) were conducted with SPSS and T-LAB, respectively. Results. The quantitative analysis revealed that the most frequent countertransference response was Helpless/Inadequate, with female therapists experiencing this more frequently than male therapists. The qualitative analysis identified two main factors explaining most of the variance in countertransference responses: Parental/Protective versus Hostile/Angry, and Positive/Satisfying versus Helpless/Inadequate, with Helpless/Inadequate central. Additionally, the qualitative analysis of treatment interruption methods revealed two factors explaining over 50% of the variance. Lack of communication was linked to negative themes, while mediated and direct communication were associated with positive terms. Direct communication was characterized as useful, while mediated communication was linked to dropout and attachment figures. Conclusion. Under pressure, psychotherapists' anxiety levels increase, often managed ambivalently or avoidantly. These results suggest that awareness of psychotherapist emotional responses is important to limit psychotherapeutic failures. These findings offer valuable insights for clinical practice.